Politik Uang, Korupsi dan Budaya OTT menjadi sebuah Tradisi di Indonesia - kristian, indra (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2024)
This paper addresses issues related to direct Regional Election (Pilkada) that have not been maximized, even triggers, including: money politics, rampant corruption and the phenomenon of OTT (capture operations) that occur in various sectors of the sector. Community questions arise, including: (1) how to eradicate money politics, (2) in what ways can a culture of corruption be eradicated (3) whether the hopes and rights of the people are represented (4) whether with direct elections can give birth to leaders with integrity ( 5) how to erase the paradigm of society that elected leaders have the opportunity to find a coffers to replace political costs and how to erase the logic of thinking about the dowry of political power. Oddities that occur in Indonesia, election participants understand the rules but still violate the rules in force. Thisresearch is a qualitative research according to the object of writing study using library research (library research). The direct election regulation in fact has not been able to minimize money politics in the elections. The hope, along with the drafting of the election law is able to provide a different color so that it becomes better in accordance with democratic election rules